Rheumatoid Arthritis Related B‐Cell Changes Are Found Already in the Risk‐RA Phase - Vries, Charlotte; Huang, Wenqi; Sharma, Ravi Kumar; Wangriatisak, Kittikorn; Turcinov, Sara; Cîrciumaru, Alexandra; Rönnblom, Lars; Grönwall, Caroline; Hensvold, Aase; Lundberg, Karin; Malmström, Vivianne (European journal of immunology, 2025)
Anti‐cyclic citrullinated peptide2 (CCP2) antibody positivity in rheumatoid arthritis (RA) and in the predisease phase, together with the success of B‐cell depletion, support a crucial role for B cells in RA pathogenesis. Yet, knowledge of B cells in the transition from autoimmunity to RA is limited, and therefore we here investigated B‐cell changes during the risk‐RA phase. B‐cell phenotypes in 18 CCP2‐positive risk‐RA individuals with musculoskeletal complaints were studied, parallel with ten CCP2‐positive RA patients and nine healthy controls. Nine of the risk‐RA individuals progressed to RA. B‐cell phenotypes were investigated using spectral flow cytometry. The results demonstrate that unswitched and switched memory B‐cell frequencies in the risk‐RA cohort were more similar to controls than RA patients. Yet, risk‐RA progressors displayed an early activation profile amongst naïve B cells. Deeper characterization of the memory compartment revealed expansion of CD27‐negative IgG+ B cells both in RA compared with controls (p = 0.0172) and in risk‐RA progressors versus non‐progressors (p = 0.0295). Overall, we demonstrate that the phenotypic distribution of B cells is altered in the risk‐RA phase. This includes changes in CD27‐negative class‐switched B cells, which have been attributed to autoreactive and anergic features implicating a possible contribution to RA development. When risk RA subjects progress to RA they display ‐a reduction in memory B cells ‐increased proportions of CD27‐negative switched IgG cells ‐increased proportions of CXCR5‐negative naïve B cells Our data suggest that extrafollicular B cell responses are involved in RA development. CXCR5‐negative aNAV B cells in the RA phase (i.e., RA progressors) may fuel the expansion of CD27‐negative class‐switched memory B cells, a process that can be related to the extra‐follicular B cell response.